Sanksi Hukum terhadap Pelanggaran Hak Cipta yang Dilakukan oleh Perusahaan Karaoke - Bayu Kusuma Permana Putra; I Nyoman Putu Budiartha; I Ketut Sukadana (Jurnal Konstruksi Hukum, 2020)
Copyright protection, especially for making music or songs, is a serious problem because there are so many pirated music or songs in Indonesia. Royalties must be given to the person who creates or owns the work because other parties use the work for sale. However, sometimes entrepreneurs who use the work of other people in their business do not make or are negligent in paying royalties which can cause harm to the copyright holder. The purpose of this study is to determine the royalty arrangements for song copyright holders in karaoke companies and to find out legal sanctions against karaoke companies that do not provide royalties to copyright holders. This research is a normative legal research with a statutory approach and a case approach. The type of data used comes from primary legal materials and secondary legal materials then analyzed by deductive-deductive logic. The results of the research show that in Law Number 28 of 2014 concerning Copyright Everyone who without rights and or without the author's permission or copyright holder violates the creator's economic rights as referred to in Article 9 paragraph (1) letter a, letter b, letter e, and / or letter g for Commercial Use, shall be punished with imprisonment of up to 4 (four) years and / or a maximum fine of Rp. 1000,000,000.00 (One Billion Rupiah).